Wnt2 is a direct downstream target of GATA6 during early cardiogenesis. - Alexandrovich, A; Arno, M; Patient, R; Shah, A; Pizzey, J; Brewer, A (2006)
The GATA4, 5 and 6 subfamily of transcription factors are potent transactivators of transcription expressed within the precardiac mesoderm. However, little is known of the immediate downstream targets of GATA-factor regulation during the earliest stages of cardiogenesis. Using the P19-CL6 embryonal carcinoma (EC) cell line as an in vitro model of cardiogenesis, we show that GATA6 is the most abundantly expressed of the GATA factors in presumptive cardiac cells. Consequently, we performed a microarray screen comparing mRNA from control EC cells, early in the cardiac differentiation pathway, with those in which GATA6 had been overexpressed. These studies identified 103 genes whose expression changed significantly and this was verified in a representative array of these genes by real-time RT-PCR. We show that early cardiac expression of one of these genes, Wnt2, mirrors that of GATA6 in vitro and in vivo. In addition, its upregulation by GATA6 in differentiating EC cells is mediated by the direct binding of GATA-factor(s) to the cognate Wnt2 promoter, suggesting Wnt2 is an immediate downstream target of GATA-factor regulation during early cardiogenesis.